Effect of GnRH 7 Days Before Presynchronization With Simultaneous PGF2α and GnRH on Reproductive Outcomes in Holstein Dairy Cows - Hubner, Andrew M.; Peixoto, Phillip M. G.; Hillesheim, Joshua; Canisso, Igor F.; Lima, Fabio S. (Frontiers in Veterinary Science, 2020)
We evaluated if an additional GnRH seven days before pre-synchronization with simultaneous PGF2α and GnRH (PG+G) would improve responses to presynchronization, synchronization, and pregnancy per AI (P/AI). We hypothesized that administering GnRH seven days before PG+G would increase ovulation and corpus luteum (CL) presence at the PG+G, improve response to OvSynch treatments and P/AI. Holstein cows were blocked by parity and randomly assigned to either a PG+G (Control, n = 205); or to GnRH followed seven days later by PG+G (ExtG, n = 201). At enrollment, Control was left untreated, whereas ExtG received GnRH. Seven days after enrollment, Control and ExtG received PG+G followed by OvSynch seven days later (GnRH, 7d PGF2α, 56h GnRH, 16h timed AI). Ovarian dynamics were assessed using ultrasonography in a subset of cows (n = 53 for Control; and n = 50 for ExtG) at each treatment, except the 2nd GnRH of OvSynch. Pregnancy diagnosed at 32- and 67-days post AI. Ovulation at enrollment tended (P = 0.06) to be higher for ExtG, but ovulation was not different at PG+G (P = 0.41) and first GnRH of the OvSynch (P = 0.25). There was a tendency (P = 0.08) for ExtG to have larger CL than Control at PGF2α of the OvSynch. There were no differences in CL and follicle sizes in any other treatment point assessed. There were no differences (P = 0.12) in luteolysis between treatments after PG+G. Overall P/AI was similar between treatments on Day 32 (Control = 33.0 % vs. ExtG = 34.6%, P = 0.75) and 67 (Control = 31.8 % vs. ExtG = 32.5%, P = 0.29) post AI. There was a tendency for an interaction between treatment and parity (P = 0.09) for P/AI at day 67 post-AI. In multiparous cows, ExtG tended to have greater P/AI than Control, whereas, in primiparous cows Control tended to have greater P/AI than ExtG at day 67 post-AI. In conclusion, the effects of GnRH seven days before PG+G presynchronization lead to positive and negative tendencies, respectively, in multiparous and primiparous cows for P/AI at day 67 post-AI and needs further investigation.